2020
DOI: 10.1002/lt.25820
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Versus Open Right Lobe Donor Hepatectomy for Adult Living Donor Liver Transplantation: A Propensity Score–Matched Analysis

Abstract: Robotic right lobe donor hepatectomy (RRLDH) is rarely performed, and data concerning its safety and efficacy are lacking. Here we compare our series of RRLDHs with a similar cohort undergoing open right lobe donor hepatectomy (ORLDH) with a propensity score-matched (PSM) analysis. Among 263 consecutive adult patients undergoing right lobe living donor hepatectomy from January 2015 until July 2019, 35 RRLDHs were matched to 70 ORLDHs. A 1:2 PSM analysis was performed to make the groups comparable for donor sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
103
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(105 citation statements)
references
References 24 publications
2
103
0
Order By: Relevance
“…While no differences were noted for postoperative complications, the robotic approach resulted in less blood loss and lower postoperative pain scores compared with the open procedure as well as better donor satisfaction with cosmetic results and body image when compared with the laparoscopic procedure. These results were confirmed by Broering et al in a series 263 consecutive adult patients undergoing right lobe living donor hepatectomy, of which 35 robotic and 70 open procedures were included in a propensity score matched analysis [49]. The safety (no conversion, all grafts successfully transplanted) was demonstrated and it was revealed that the robotic approach was associated with equally low complications, reduced blood loss, diminished uses of patient-controlled analgesia and a shorter hospital stay.…”
Section: Future Perspectivesmentioning
confidence: 62%
“…While no differences were noted for postoperative complications, the robotic approach resulted in less blood loss and lower postoperative pain scores compared with the open procedure as well as better donor satisfaction with cosmetic results and body image when compared with the laparoscopic procedure. These results were confirmed by Broering et al in a series 263 consecutive adult patients undergoing right lobe living donor hepatectomy, of which 35 robotic and 70 open procedures were included in a propensity score matched analysis [49]. The safety (no conversion, all grafts successfully transplanted) was demonstrated and it was revealed that the robotic approach was associated with equally low complications, reduced blood loss, diminished uses of patient-controlled analgesia and a shorter hospital stay.…”
Section: Future Perspectivesmentioning
confidence: 62%
“…The robotic platform also has the added benefits of overcoming restrictions in range of motion, physiological tremor and a limited field of vision. The high resolution amplified 3D image, tremor filtration and additional degrees of freedom of instruments allow for meticulous tissue handling, precise dissection and easier suturing capabilities[ 13 - 15 , 29 , 44 ]. All of which are important pre-requisites of a safe LD operation.…”
Section: Advantages Of Rdhmentioning
confidence: 99%
“…They found 2 studies suggesting the superiority of machine learning techniques to standard liver scoring modalities for liver graft outcome. • Robotic donor hepatectomy: Broering et al 59 Thirty-five live liver donors undergoing robotic-assisted right hepatectomy were compared with propensity-matched (1:2) donors with open donor right hepatectomy. Donor complications were similar.…”
Section: Machine Perfusionmentioning
confidence: 99%
“…Importantly, donors undergoing robotic surgery required less patient-controlled analgesia and had a shorter hospital stay compared with the open surgery group. 59 The group from Yonsei University College of Medicine, Seoul, South Korea, also reported the comparison among robotic living donor right hepatectomy (n = 52), conventional open donor right hepatectomy (n = 62), and laparoscopy-assisted donor right hepatectomy (n = 118). They reported that the robotic method resulted in less blood loss compared with that of the open method.…”
Section: Liver Transplantationmentioning
confidence: 99%